Construction of a Necroptosis-Related miRNA Signature for Predicting the Prognosis of Patients With Hepatocellular Carcinoma - Meng, Tongyu; Wang, Qingfeng; Yang, Yufeng; Ren, Yanling; Shi, Yan (Frontiers in Genetics, 2022)
Background: Many miRNAs have been demonstrated to be associated with prognosis of hepatocellular carcinoma (HCC). However, how to combine necroptosis-related miRNAs to achieve the best predictive effect in estimating HCC patient survival has not been explored. Methods:The mRNAs and miRNAs expression profile were downloaded from public database (TCGA-LIHC cohort). Necroptosis-related genes were obtained from previous references and necroptosis-related miRNAs were identified using Pearson analysis. Subsequently, differential expression miRNAs (DEms) were identified in HCC and paracancer normal samples based on necroptosis-related miRNAs expression. The whole set with HCC were randomized into training set and testing set (1:1). LASSO-Cox regression analysis was used to construct a miRNAs signature. Multiple statistical methods were used to validate the clinical benefit of signature in HCC patients, including receiver operator characteristic (ROC) curves, Kapla-Meier survival analyses, decision curve analysis (DCA) curves. Downstream target genes of miRNAs were obtained from different online tools, and the potential pathways involved in miRNAs were explored. Finally, we conducted RT-qPCR in SK-HEP-1, THLE-3 and HUH-7 cell lines for miRNAs involved in signature. Results: The results showed that a total of 8 specific necroptosis-related miRNAs were screened between HCC and adjacent tissues in training set. Subsequently, based on the above-mentioned miRNAs, 5-miRNAs signature (miR-139-5p, hsa-miR-326, miR-10b-5p, miR-500a-3p, and miR-592) was generated by LASSO-Cox regression analysis. Multivariate Cox regression analysis showed that riskscore were independent prognostic indicators in each set. The area under curves (AUCs) of 1-year, 3-years, 5-years, and 7-years were high in each set (AUC >0.7). DCA analysis also revealed that risk score had a potential benefit than other clinical characteristics. Meanwhile, survival analysis showed the high-risk group showed low survival probabilities. Moreover, the results of enrichment analysis showed that specific miRNAs mainly enriched in cAMP signaling pathway, and TNF signaling pathway, etc. Finally, the results of RT-qPCR were consistent with the prediction results in public databases. Conclusion: Our study establishes a robust tool based on 5- necroptosis-related miRNAs for prognostic management of HCC patients.